CAD Design for Recycling and Utilization of Waste Packaging from the Perspective of Ecological Criticism - Jia Wen (Advances in Multimedia)
In order to realize the value of packaging waste through recycling, detection, classification, maintenance, and reprocessing, the model construction and simulation study of logistics packaging recycling and utilization were put forward. This paper takes logistics companies as the research object, aiming at the business model of logistics companies, uses the Internet of things recycling machine for packaging recycling, and establishes a dual channel packaging recycling model. This model is intended to compare and analyze the difference between traditional packaging waste recycling channel and intelligent recycling machine of the internet of things in terms of recycling cost, profit, recovery rate, waste incineration rate, and other aspects. It is assumed that the recycling proportion of the two channels accounts for half of the packaging waste. The results of simulation analysis on recycling and utilization of dual-channel packaging waste show that in the simulated time period, the recycling rate of the intelligent recycling machine using the internet of things is higher than that of the traditional dispersed recycling vendors. Assume that when the recycling frequency = 2, when the recycling frequency is increased to 2 times a day, the recycling time of the internet of things recycling machine is further shortened, and the recycling efficiency is improved. At the same time, due to the improvement of the recycling rate of the internet of things recycling machine, the amount of waste packaging decreases, so the recycling rate of the dispersed recycling vendors decreases accordingly. The recycling revenue and net profit generated by channel 2 (internet of things recycling machine) are higher than those generated by channel 1 (decentralized recycling vendor responsible for recycling). The average profit of channel 2 is about 28,163.69 yuan, while the average profit of channel 1 is only 9,395.89 yuan. The waste recovered through channel 2 is lower than that in channel 1; the average for channel 1 is 15.58 tons. However, the average value of channel 2 is 14.58 tons. Comprehensive analysis shows that channel 2 has obvious advantages in reducing waste discharge. However, it is necessary to strengthen the research and development of recycling technology, improve the reuse efficiency, and reduce the incineration of nonreusable waste as much as possible to the minimum, which proves the robustness of this paper to the logistics packaging recycling model construction. It is proved that the robustness of this paper for logistics packaging recycling model construction provides strong support for the analysis of waste pallets and packaging recycling-related issues.